Návrh investic do akcií světových tabákových společností pro doplnění portfolia ETF - Obůrka, Josef (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Diplomová práce je věnována doporučení doplnění Exchange Traded Fund o akcie společností tabákového průmyslu. Kapitola teoretických východisek práce popisuje blíže ETF, investice a všechny druhy ukazatelů použité v analytické části. Analytická část postupuje od výběru společností, přes samotnou analýzu až k verifikaci společností. Ve vlastních návrzích jsou představeny doporučené společnosti, ale také předpokládaný vývoj odvětví a soudobá rizika investování do akcií.

The diploma thesis is dedicated to the recommendation of supplementing the Exchange Traded Fund with shares of tobacco industry companies. The chapter of the theoretical basis of the work describes in more detail ETFs, investments and all kinds of indicators used in the analytical part. The analytical part proceeds from the selection of companies, through the analysis itself, to the verification of companies. Recommended companies, as well as anticipated industry developments and current risks of investing in shares, are presented in our own proposals.
Proposal for Investments in the Shares of Global Tobacco Companies to Complement the ETF Portfolio
Keywords: Investice; ETF; tabákový průmysl; akcie; analýza; verifikace; hodnocení; riziko; Investments; ETF; Tobacco industry; stocks; analysis; verification; evaluation; risk